Interindustry Variation in the Costs of Job Displacement - Carrington, William J.; Zaman, Asad (Journal of Labor Economics, 1994)
Job displacement entails a substantial wage reduction for most displaced workers. We show that the mean reduction, the tenure profile of reductions, and the experience profile of reductions all vary substantially across industries. We then link this interindustry variation to analogous variation in firm size, unionization, wage levels, and the incidence of employer-provided training. While these industry characteristics explain some of the interindustry variation in mean wage reductions, they do not explain variation in the tenure or experience profiles of wage reductions.